About Specific Training of a Foreign Audience in Russian - Makhmadieva Gulchekhra Sait-Abdullaevna (Zien Journals, 2021)
All words of the English language are divided into certain lexical and grammatical categories, called parts of speech. Parts of speech are the main lexicographic categories into which words of a language are distributed based on the following characteristics: a) semantic (generalized meaning of an object, action or state, quality), b) morphological (morphological categories of a word), and c syntactic (syntactic functions of a word)
Keywords: English language; lexical and grammatical categories; divided; syntactic